Proposta de preservação digital: o caso do acervo de um arquivo universitário visando à perenidade documental - Reis, Auricelia França de Souza (2024)
The history of archives dates back to the records of events made by the first civilizations, in different supports and forms, such as, for example, prehistoric images, engravings, papyrus, clay plaques, including paper recording (textual and image information). Currently, with scientific and technological advances, the variety of these supports and informational forms has increased as a result of this development. In the contemporary context, we live with many documents recorded in digital and electronic media that are stored in “clouds” or in document organization systems. Despite all these advances, even so, the need for information management within the scope of document management is increasingly perceived, especially in digital archives, since with human development, the supports will become irremediably obsolete. It is, therefore, in this context that this research will be carried out with the following guiding question: How to define and manage a set of criteria that contribute to the evaluation of the process of digital preservation of archival documents aiming at the preservation of organizational memory? Faced with the guiding question, the qualitative research has the general objective of identify and managing a set of criteria that contribute to the evaluation of the process of digital preservation of archival documents aimed at preserving organizational memory. As for the nature, the research is classified as descriptive exploratory. As data collection tools, we chose to use the Google Forms online questionnaire and simple observation. Data collection will be used in bibliographic sources and we will adopt the application of a questionnaire with the servers and researchers of the archive in locus, as well as we carry out the simple observation to reach the results presented here. With the completion of the steps provided for by the proposed method, is it intended to identify what difficulties and challenges the file in question faces to carry out the preservation of digital memory?